Studi Komparatif Kinerja Keuangan Daerah Induk dan Daerah Pemekaran (Kabupaten/Kota di Provinsi Jambi) - Endah Tri Kurniasih; Etik Winarni; Ahmad Soleh (J-MAS (Jurnal Manajemen dan Sains), 2020)
Based on Law No. 33/2004 on the transfer of power from the central government to the local government in managing, collecting and managing the source of receipt in accordance with the potential and conditions of their respective regions or seized by fiscal decentralization. In order to realize this goal, local governments are allowed to carry out regional expansion. The purpose of the expansion is to optimize services to the community in light of the growing population development. To improve service performance, it is certainly required to have sufficient financial capabilities. In order to ensure the implementation of the implementation, the financial capabilities of each region are required, but regional autonomy often creates fiscal gaps and becomes a burden on the central government as a result of the inability to finance development carried out by local governments. Therefore, efforts are needed to improve and find alternative sources of new admissions taking into account the conditions and potential that exist in each area. On the basis of the problem, this research needs to be carried out to see if the implementation of regional autonomy has been effectively carried out in accordance with the objective of regional autonomy which is to achieve fiscal independence. The objectives of this study are (1) analyzing the financial capabilities of the expansion area and the parent region (2) analyzing how the new and parent districts receive efforts in the implementation of fiscal maturity. The data used in this study is secondary data of danalm bentum time series in the period 2009-2017 sourced from Dispenda, BPS and related agencies from 11 districts / cities in Jambi Province. Analysis of data used by nature of this study with models of fiscal decentralization degrees (FDD), Regional Spending Performance and Regional Financial Retdor. While to measure tax efforts used the Tax Ratio and Tax Capacity model.